Women's labor force participation in rural India: Current status, patterns and drivers - Joshi, Kuhu; Joshi, Chaitanya K.; Kishore, Avinash (International Food Policy Research Institute, 2019)
Women’s labor force participation (LFP) has been consistently low over the past three decades in India. This is despite rapid economic growth, better educational attainment, and a decline in fertility. The literature predicts a U-shaped relationship between economic growth and women’s LFP. As a country’s income increases, women who were engaged in sustenance-work, usually involving manual labor, drop out of the labor force. They re-join the labor force after receiving education and gaining access to white collar jobs. However, India is an extreme outlier compared to other developing countries of similar wealth levels.